Rhizaxinella strongylata Bertolino & Costa & Bavestrello & Pansini & Daneri 2020, sp. nov. - Bertolino, Marco; Costa, Gabriele; Bavestrello, Giorgio; Pansini, Maurizio; Daneri, Giovanni (Zenodo, 2020)
Rhizaxinella strongylata Bertolino, Costa & Pansini sp. nov. urn:lsid:zoobank.org:act: 78052288-83C4-4D9F-91DE-6275C19187CE Fig. 14 Etymology The new species is so named for the presence of strongyloid styles in the spicules. Type material Holotype CHILE – Puerto Cisnes • Seno Magdalena D; 44.614863° S, 72.958312° W; depth 25 m; 5–10 Aug. 2016; Marco Bertolino leg.; on a vertical wall by scuba diving; CILE 65; MSGN 61499. Description HABITUS. Small erect sponge, 5 cm high, with thin stalk (5 mm in diameter) which divides into two branches with peariform extremities (Fig. 14A). Two round oscula visible. Surface hispid. Colour in life bright yellow (Fig. 14A). Consistency strong but compressible. SKELETON. Stalk characterized by axial compact skeleton that diverges into thinner secondary axes in branches. Close to surface ectosomal skeleton composed of brushes of spicules. SPICULES. Megascleres: Smooth, slightly curved, long tylostyles (Fig. 14B), 841.5–(1466.3)–2320.5 μm long and 17.5–(21.75)–30 μm thick. Shorter, straight or curved, often fusiform tylostyles, with different heads (Fig. 14C), 175–(230.25)–320 μm long and 10–(14.1)–17.5 μm thick. Smooth strongyloid styles, more or less curved (Fig. 14D), 200–(274.55)–340 μm long and 10–(18.75)–25 μm thick. Habitat Species lives at a depth between 20 and 25 m on a vertical wall. Remarks Only one species of this genus has been reported from the channels and fjords of southern Chile: Rhizaxinella spiralis (Ridley & Dendy, 1886). The new species R. strongylata sp. nov. described here differs from R . spiralis in external morphology, shape and size of styles/tylostyles, and in the presence of strongyloid spicules. In fact, R . spiralis has a stipitate cylindrical shape and two categories of tylostyles/styles that measure 1000 × 13 μm and 400 μm (width not reported in original description). Four other Rhizaxinella species are present in the Southern Hemisphere and so geographically closer to the new species. Rhizaxinella australiensis Hentschel, 1909 (North Patagonian Gulf, East Antarctic Wilkes Land, West Australia) is ramified with vertical branches; tylostyles are sinuous, straight or strongyloid and measure 500–1200 × 9–19 μm and 240–500 × 9–12 μm. Rhizaxinella dichotoma Lévi, 1993 (New Zealand, New Caledonia) is pedunculate with multiple branches, has principal tylostyles (725–1200 × 15–30 μm) and peripheral tylostyles (400–800 × 4–10 μm). Rhizaxinella durissima (Ridley & Dendy, 1886) (Southwest Australia) with pedunculate shape has straight styles/tylostyles (240 × 6.3 μm) and fusiform tylostyles (1500 × 15.7 μm). The species morphologically closest to the new species, based on the large spicules and the presence of strongyloid forms, appears to be R . radiata Hentschel, 1909 (West Australia) which has a pedunculate shape, straight styles (1100–2150 × 27–45 μm), styles/subtylostyles (250–800 × 10–17 μm) and strongyles (250–350 × 7–11.2 μm). Even allowing for the lesser importance of sponge shape and a degree of morphological variability within the genus, the present description of type and size of spicules of R. strongylata sp. nov. merits the establishment of a new species. : Published as part of Bertolino, Marco, Costa, Gabriele, Bavestrello, Giorgio, Pansini, Maurizio & Daneri, Giovanni, 2020, New sponge species from Seno Magdalena, Puyuhuapi Fjord and Jacaf Canal (Chile), pp. 1-49 in European Journal of Taxonomy 715 on page 36, DOI: 10.5852/ejt.2020.715, http://zenodo.org/record/4022397